Investigation of the Parametric Properties of the Flanging Operation for Stainless Steels with Finite Element Analysis and Experimental Design Approach - Saray, Onur; Efe, Uğur; Fırat, Ömer (Osman SAĞDIÇ, 2022)
In this study, Taguchi's experimental design and finite element analysis were used to determine relationships between the geometrical properties of the punch-die pair and flange dimensions. Results of the study showed that the highest values of both flange wall thickness and flange length could be achieved when punch taper length, die taper angle and pilot hole diameter took values of 3.5 mm, 90°, and 2.75 mm, respectively. When the relationship between the process parameters and the deformation behavior was examined, a more substantial effect of punch taper length on the deformation behavior of the process was detected. The decrease in values of the punch taper length is found necessary to simultaneously increase flange length and flange wall thickness. However, it was realized that this could also cause forming problems, such as smearing the material due to high contact pressures.

Bu çalışmada, ferritik paslanmaz çeliklere uygulanan flanşlama operasyonlarında kullanılacak zımba-kalıp çiftlerinin geometrik özellikleri ile elde edilen flanşlara ait geometrik özellikleri arasındaki ilişkiler Taguchi deney tasarımı ve sonlu elemanlar analizleri kullanılarak incelendi. Bu kapsamda hem flanş et kalınlığı hem de flanş boyunun en büyük değerlere ulaşması için zımba koniklik boyu, kalıp koniklik açısı ve pilot delik çapının sırasıyla 3,5 mm, 90° ve 2,75 mm değerini alması gerektiği anlaşıldı. Proses parametrelerinin deformasyon davranışı ile ilişkisi incelendiğinde ise, proses davranışını en çok zımba koniklik boyunun etkilediği görüldü. Bu faktörün mümkün olan en küçük değerler alması halinde, flanş boyu ve flanş et kalınlığının bir arada büyük değerlere taşınabileceği anlaşıldı. Ancak bunun aynı zamanda malzemenin sıvaması gibi şekillendirme problemlerine neden olabileceği anlaşıldı.
Paslanmaz Çeliklere Uygulanan Flanşlama Operasyonunun Parametrik Özelliklerinin Sonlu Elemanlar Analizleri ve Deney Tasarımı Yaklaşımımı ile İncelenmesi
Keywords: Engineering; Mühendislik